Prognostic value of right ventricle to pulmonary artery coupling in transcatheter aortic valve implantation recipients. Issue 9 (10th September 2022) - Adamo, Marianna; Maccagni, Gloria; Fiorina, Claudia; Giannini, Cristina; Angelillis, Marco; Costa, Giulia; Trani, Carlo; Burzotta, Francesco; Bruschi, Giuseppe; Merlanti, Bruno; Poli, Arnaldo; Ferrara, Erica; et al.
Abstract : Aims: To investigate the impact of the right ventricle to pulmonary artery (RV-PA) coupling on the outcome of patients undergoing transcatheter aortic valve intervention (TAVI), and to describe changes in right ventricular function, pulmonary hypertension, and their ratio after TAVI. Methods: Three hundred and seventy-seven patients from the Italian ClinicalService Project, who underwent TAVI between February 2011 and August 2020, were included. Tricuspid annular plane systolic excursion/pulmonary artery systolic pressure (TAPSE/PASP) ratio was retrospectively calculated as a surrogate of RV-PA coupling. The population was stratified according to TAPSE/PASP using a cut-off of 0.36 mm/mmHg derived from a receiving operating characteristic (ROC) curve. The primary end point was 6-month all-cause death. Results: Compared with patients with a TAPSE/PASP ratio ≥0.36 mm/mmHg (81%), those with TAPSE/PASP ratio <0.36 mm/mmHg (19%) had more comorbidities and were more symptomatic. Moreover, they were more likely to receive general anesthesia and an old generation device. Device success was similar between the two groups. A TAPSE/PASP ratio <0.36 mm/mmHg was associated with a higher risk of all-cause death at 6-months (17.3% versus 5.3%; adjusted HR 2.66; P = 0.041). The prognostic impact of the TAPSE/PASP ratio was stronger than the impact of TAPSE and PASP as separate parameters and was independent of the surgical risk score. Both TAPSE, PASP, and their ratio improved from baseline to 1 month and 6 months after TAVI. Conclusions: A TAPSE/PASP ratio <0.36 mm/mmHg is strongly associated with an increased risk of mortality after TAVI. Providing a left ventricle unloading, TAVI is associated with improvement of both TAPSE, PASP, and their ratio.